Three‐day postoperative antibiotics reduces post‐hepatectomy infection rate in hepatitis B virus‐related hepatocellular carcinoma. Issue 9 (21st May 2021) - Chen, Zebin; Jiang, Hong; Wang, Yuanqi; Liang, Ruiming; Xu, Lixia; Lai, Jiaming; Shen, Jingxian; Li, Jiali; Li, Dongming; Li, Shaoqiang; Lei, Kai; Zhou, Qian; et al.
Abstract: Background and Aim: The evidences for use of postoperative antibiotics (POA) in hepatocellular carcinoma (HCC) patients who underwent hepatectomy are controversial. We aimed to explore the relationship between POA and hepatectomy‐related infection in a hepatitis B virus (HBV)‐related HCC population. Methods: We retrospectively collected 934 HCC patients who underwent hepatectomy for curative intent from three tertiary hospitals in China. The incidences of postoperative infection including surgical site infection and remote site infection were recorded and calculated. Univariable and multivariable logistic regression analyses were performed to explore related factors of postoperative infection and POA. And the relationship between infection rates with different durations of POA was investigated. Results: The overall infection rate was 8.2% (77/934), including 6.5% (61/934) of surgical site infection and 2.0% (19/934) of remote site infection. Multivariable analysis revealed that the administration of POA was negatively related with the incidence of postoperative infection significantly (odds ratio = 0.50, 95% confidence interval = 0.30 to 0.83; P  = 0.008). Albumin‐bilirubin score, Barcelona Clinic Liver Cancer (BCLC) stage and extent of hepatectomy were independently related to the POA. And 3‐day regimen seemed to be the shortest duration of POA to gain the lowest incidence of postoperative infection. Conclusions: Postoperative antibiotic is necessary for HBV‐related HCC patients to prevent postoperative infection, especially for those with higher albumin‐bilirubin score, at BCLC stage B–C, or who underwent major hepatectomy. For HBV‐related HCC patients, postoperative second‐generation cephalosporins, or ceftriaxone for 3 days after surgery might be proper.